Obesity and diabetes are the strongest predictors of post-acute COVID-19 in Coptic clergy and monks - Henein, Michael Y.; Shenouda, Rafik; Matter, Magdi; Bytyçi, Ibadete (Archives of Clinical and Biomedical Research, 2022)
Background and Aims: In contrast to priests, the life style of monks is almost similar, irrespective of their order and specifics of religious practices. The aim of this study was to assess the cardiac risk factors in Coptic priests and monks and their impact on post- acute COVID-19. Methods: Of 1519 clergy, participating in the COVID-19-Clergy study, serving in Europe and Egypt, 257 had the infection and were included in this analysis. Clergy were divided into priests (n=204) and monks (n=53). Participants’ demographic indices, cardiovascular risk factors, management details and post-acute COVID-19 duration were assessed. The impact of geographic differences of life style were also analysed. Results: Priests were more obese (p=0.001), had more type 2 diabetes (DM) (p=0.001), arterial hypertension (AH) (p<0.001), dyslipidemia (p=0.001) and lower prevalence of infection (p<0.001) compared to monks. Their symptoms’ duration was more prolonged (p<0.001), had frequent post-acute COVID (p<0.001) and had greater need for hospital treatment (p=0.04). In a sub-analysis, priests serving in Europe had higher prevalence of AH, DM, obesity, CHD, dyslipidemia, longer symptoms duration and more frequent post-acute COVID compared to monks from Europe (p<0.05 for all). Similarly, those risk factors were higher in priests serving in Northern Egypt compared to local monks (p<0.05 for all). Symptoms’ duration correlated directly with severity of obesity (rpb = 0.54, p=0.001) and frequency of diabetes (rpb = 0.58, p<0.001). In multivariate analysis, DM 2.56 [(1.189 to 5.524); p=0.01] and morbid obesity OR 2.11 [(1.109 to 4.923); p=0.02] predicted post-acute COVID-19 in the Coptic clergy, particularly priests, while age and moderate obesity were the main predictors in monks (p<0.05 for all).</